2021
DOI: 10.1002/advs.202102213
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial “Anchoring Effect” Enables Efficient Large‐Area Sky‐Blue Perovskite Light‐Emitting Diodes

Abstract: While tremendous progress has recently been made in perovskite light-emitting diodes (PeLEDs), large-area blue devices feature inferior performance due to uneven morphologies and vast defects in the solution-processed perovskite films. To alleviate these issues, a facile and reliable interface engineering scheme is reported for manipulating the crystallization of perovskite films enabled by a multifunctional molecule 2-amino-1,3-propanediol (APDO)-triggered "anchoring effect" at the grain-growth interface. Sky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 47 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…Apart from the electrical influences of the CsAc layer on the carrier dynamics, we conjected that the CsAc layer may also function as a surface modifier, which can improve the properties of perovskites as well. Surface modification on the transport layer has been demonstrated to be effective in enhancing the crystallinity of perovskites and improving the carrier transport capability . Therefore, we also conducted structural and optical investigations on the perovskite film without and without the CsAc layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the electrical influences of the CsAc layer on the carrier dynamics, we conjected that the CsAc layer may also function as a surface modifier, which can improve the properties of perovskites as well. Surface modification on the transport layer has been demonstrated to be effective in enhancing the crystallinity of perovskites and improving the carrier transport capability . Therefore, we also conducted structural and optical investigations on the perovskite film without and without the CsAc layer.…”
Section: Resultsmentioning
confidence: 99%
“…Surface modification on the transport layer has been demonstrated to be effective in enhancing the crystallinity of perovskites and improving the carrier transport capability. 42 Therefore, we also conducted structural and optical investigations on the perovskite film without and without the CsAc layer.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) characterizations were conducted to analyze charge transport and recombination behaviors in the our fabricated QLEDs. , Figure b shows the Nyquist plots of QLED devices based on the pristine TFB and the cross-linked TFB:X1 under a forward bias voltage of 3.0 V. The inset of Figure b is the simplified equivalent circuit model, consisting of capacitors and parallel and series resistors. The serial resistance ( R s ) represents the total external resistance including the electrodes, the external wires, and the contact resistance between the electrode and the functional layer.…”
Section: Resultsmentioning
confidence: 99%
“…17 The rational selection of the interface layer material can regulate the crystallization of the perovskite, 18 align the energy level, 19 reduce interface defects, 20,21 and prevent the interfacial reaction and ion migration from the perovskite film to the transport layer or to the electrode. 22 Tang et al incorporated potassium sulfate (K 2 SO 4 ), 18 amino-functionalized ethanolamine (ETA), 23 and 2-amino-1,3-propanediol (APDO) 24 into the PEDOT:PSS solution. Their experimental results showed that all three molecules reduced the contact angles of the precursor solutions on PEDOT:PSS film to a certain extent and improved the hydrophilicity of the PEDOT:PSS substrate.…”
Section: Introductionmentioning
confidence: 99%